东亚国家产业政策对河北省的启示 = The implications of the industrial policy of South Asian countries to Hebei province, China - 马志新 Ma, Zhixin (2008)
Based on the economic theories of industrial development and the successful experiences of the East Asian countries, this thesis empirically analyzed the industrial structure of Hebei province and found that it is currently enjoying great potentials and comparative advantages in seven industries, namely metal, building material, chemical, food, pharmaceutical, machinery, and textile industries.